Development of bread wheat genotypes for multiple resistance to foliar diseases - Al-Jaboobi, Muamar; Tadesse, Wuletaw; Louriki, Sara; Zakaria, EL Gataa; Kemal, Seid Ahmed (2024)
Global food security and sustainable wheat production are both constantly threatened by increased human population. Yellow rust (Puccinia striiformis f. sp. tritici) stem rust (P.graminis f. sp. tritici) and Septoria tritici blotch , ((Zymoseptoria tritici) are the major challenges for sustainable wheat production in different countries around the world. The three wheat rusts are the most damaging diseases in world and continue threatening global food security ( Bhavani et al. 2022). Genetic resistance is the key objective of the bread breeding program. Many varieties are released in many countries and losses of resistance